Hubungan Pemberian ASI Eksklusif Dengan Kejadian Diare Pada Bayi Usia 0-6 Bulan - Puteri, Sri Kurnia Sah; Sumarmi, Sumarmi; Mantasia, Mantasia; Kartini, Anita; Dewi, Dewi (Barongko: Jurnal Ilmu Kesehatan, 2023)
Exclusive breastfeeding is essential to protect babies/children from the risk of infectious diseases. Diarrhea, which is the contagious disease that causes mortality and morbidity in second place in children under five years of age (toddlers), is thought to be related to the low level of exclusive breastfeeding. This research aims to determine the relationship between exclusive breastfeeding and the incidence of diarrhea in babies aged > 0-6 months. This type of research is an observational analysis using a cross-sectional design and a retrospective approach. The research population came from babies at the Barana Community Health Center in 2023. The research sample was 66 babies. Analysis of the relationship between variables was carried out using the chi-square test. The research results were obtained from 66 respondents; 6 (20.7%) babies were exclusively breastfed and suffered from diarrhea, and 23 (34.8%) did not suffer from diarrhea. Meanwhile, 29 (43.9%) babies who were not exclusively breastfed suffered from diarrhea, and only 8 (12.1%) did not suffer from diarrhea. The results of the chi-square test obtained a p-value = 0.000. The research conclusion shows that exclusive breastfeeding is related to the incidence of diarrhea in babies aged 0-6 months.